Medical Concepts with Clinical-Epidemiological Implications that have to be Re-Assessed Since the Coronavirus Disease 2019 (Covid-19) Pandemic - Luis Turabian, Jose (International Journal of General Practice, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is something new that baffles us. The dominant health model and the theory that supported it until before COVID-19 are refuted or invalidated by observing the current tragically situation, which also implies lasting changes in that new medical model. Consequently, once the urgency of the epidemic is over, the conceptual and organizational building of medical care can no longer be rebuilt in the same way. Based on the COVID-19 experience, it is necessary to rethink what kind of knowledge can emerge. Some of the concepts with clinical-epidemiological implications that have to be re-evaluated since the COVID-19 pandemic are: 1. Large epidemics or changes do not arise from an event similar to the "Big Bang", but rather they develop slowly and underground, so a surveillance system must be instituted; 2. Re-evaluate what we understand by "evidence-based medicine"; 3. Patient-centered care is inadequate and must be replaced by community-centered care; 4. Telecare and changes in the organization of consultations; 5. Hospitals and health centers are "biological bombs" that act as vectors of disease and must change their architecture, organization and use; 6. The end of the nursing home model; 7. Change of habits; and 8. Social media can democratize information and help communities organize.
Keywords: COVID-19; General Practice; Epidemiology; Population Surveillance/methods; Public Health Practice